Metallothionein-Like Proteins and Energy Reserve Levels after Ni and Pb Exposure in the Pacific White Prawn Penaeus vannamei - Gabriel Nunez-Nogueira; Catherine Mouneyrac; Alice Muntz; Laura Fernandez-Bringas (Journal of Toxicology)
This study analyzed the changes in metallothionein-like proteins (MTLPs) and Energy Reserves (ERs) in hepatopancreas and abdominal muscle of the white prawn Penaeus vannamei. Realistic metal concentration exposure for 10 days to Ni and Pb in solution revealed that juvenile prawns partially induce MTLP in hepatopancreas after Pb exposure. Ni was distributed equally between soluble and insoluble fractions, while Pb was present only in the insoluble fraction, suggesting different detoxification strategy. No changes in lipids and glycogen concentration were detected under these experimental conditions in both tissues analyzed. MTLP could not be considered as a suitable indicator for lead exposure in hepatopancreas.